Evaluation of Masticatory Function in Elderly Complete Denture Wearers under Nursing Care - Fukuda, Michiaki; Yamauchi, Mutsuo; Ogawa, Masayuki; Tanahashi, Masashi; Kim, Seung-Hyo (Ronen Shika Igaku, 1997)
The masticatory function of elderly complete denture wearers who needed care in daily life was compared with that of those who were self-supporting. The subjects in this study were complete denture wearers at least in either the upper or lower jaw, who were accommodated in special homes for the aged in Shiga Prefecture or who were either admitted or regularly recalled to affiliated clinics of the homes. These dentures had no abnormalities about the fittness and occlusion. Of these subjects, 29 who needed help in some spheres of daily life but were capable of cleaning their dentures without help were assigned to a dependent group (5 males and 24 females, mean age 80.6 years) and 25 who were physically self-supporting to a control group (1 male and 24 females, mean age 78.2 years). They were requested to fill in the food consumption table designed by Ushida (1992) to determine their dietary capabilities for calculating food-ingestion rates. In addition, the occlusal ares and occlusal force were measured using an “Dental Prescale 30H” (Fuji film). The occlusal area was 17.9±11.3mm2 (mean±1 standard deviation) in the dependent group and 19.0±11.2mm2 in the control group.The occlusal force was 104.0±65.9N in the dependent group and 104.0±55.2N in the control group.The food-ingestion rate was 61.9±17.5% in the dependent group and 61.3±13.8% in the control group.However, no significant differences were found between the two groups. In addition, no significant correlations were found between the food-ingestion rate and the occlusal area and between the food-ingestion rate and the occlusal force in the both groups. The above results suggest that the masticatory function of even elderly complete denture wearers under nursing care does not differ from that of elderly complete denture wearers who are self-supporting.